Interactions of DNA binding ligands with PNA-DNA hybrids. - Wittung, P (1994)
The interactions of two representative mixed-sequence (one with an AT-stretch) PNA-DNA duplexes (10 or 15 base-pairs) and a PNA2/DNA triplex with the DNA binding reagents distamycin A, 4',6-diamidino-2-phenylindole (DAPI), ethidium bromide, 8-methoxy-psoralen and the delta and lambda enantiomers of Ru(phen)2-dppz2+ have been investigated using optical spectroscopic methods. The behaviour of these reagents versus two PNA-PNA duplexes has also been investigated. With triple helical poly(dA)/(H-T10-Lys-NH2)2 no significant intercalative binding was detected for any of the DNA intercalators, whereas DAPI, a DNA minor groove binder, was found to exhibit a circular dichroism with a positive sign and amplitude consistent with minor groove binding. Similarly, a PNA-DNA duplex containing a central AATA motif, a typical minor groove binding site for the DNA minor groove binders distamycin A and DAPI, showed binding for both of these drugs, though with strongly reduced affinity. No important interactions were found for any of the ligands with a PNA-DNA duplex consisting of a ten base-pair mixed purine-pyrimidine sequence with only two AT base-pairs in the centre. Nor did any of the ligands show any detectable binding to the PNA-PNA duplexes (one containing an AATT motif). Various PNA derivatives with extentions of the backbone, believed to increase the flexibility of the duplex to opening of an intercalation slot, were tested for intercalation of ethidium bromide or 8-methoxypsoralen into the mixed sequence PNA-DNA duplex, however, without any observation of improved binding. The importance of the ionic contribution of the deoxyribose phosphate backbone, versus interactions with the nucleobases, for drug binding to DNA is discussed in the light of these findings.